PROTECTIVE ROLE OF GINGER ON LEAD INDUCED DERANGEMENT IN PLASMA TESTOSTERONE AND LH LEVELS OF MALE SPRAGUE DAWLEY RATS - Riaz, Fatima; Khan, Umar Ali; Ayub, Muhammad; Shaukat, Saffia (Journal of Ayub Medical College Abbottabad, 2011)
Background: Lead is one of the most serious environmental threats to human health especially in developing countries. It damages multiple body systems including the reproductive system. Ginger’s antioxidant and androgenic activity is reported in multiple animal studies. The aim of this study was to investigate the ameliorative effect of Zingiber officinale (ginger) on lead induced derangement in plasma testosterone and luteinizing hormone (LH) levels of male rats. Methods: Sixty adult male Sprague Dawley rats were used in this study in four groups. Group A served as normal control, Group B received 0.3% lead acetate in drinking water, Group C and group D received supplementary 0.5 and 1 gm/Kg bodyweight of ginger respectively along with lead acetate in drinking water. Five rats from each group were sacrificed at the end of 2nd, 4th and 6th weeks. Serum testosterone and LH levels were analysed using ELISA technique. Results: After co administration with different doses of ginger, serum testosterone level which was significantly decreased in lead treated group, showed a significant rise as compared to lead treated group. LH levels which had exhibited no significant change by lead treatment, after co administration with different doses of ginger, again showed no significant change. Conclusion: Oral administration of ginger ameliorated lead induced testicular toxicity in male rats by increasing serum testosterone level at all durations which might be a product of both its androgenic and antioxidant properties. Keywords: Lead toxicity, testosterone, luteinizing hormone, Zingiber officinale, male rats, antioxidant